Impetigo: incidence and treatment in Dutch general practice in 1987 and 2001-results from two national surveys - Koning, S.; Mohammedamin, R.S.A.; Van Der Wouden, J.C.; Van Suijlekom-Smit, L.W.A.; Schellevis, F.G.; Thomas, S. (British journal of dermatology (1951), 2006)
Summary Background  Impetigo is a common skin infection in children. The epidemiology is relatively unknown, and the choice of treatment is subject to debate. Objective  The objective of our study was to determine the incidence and treatment of impetigo in Dutch general practice, and to assess trends between 1987 and 2001. Methods  We used data from the first (1987) and second (2001) Dutch national surveys of general practice. All diagnoses, prescriptions and referrals were registered by the participating general practitioners (GPs), 161 and 195, respectively. Results  The incidence rate of impetigo increased from 16·5 (1987) to 20·6 (2001) per 1000 person years under 18 years old (P < 0·01). In both years, the incidence was significantly higher in summer, in rural areas and in the southern region of the Netherlands, compared with winter, urban areas and northern region, respectively. Socioeconomic status was not associated with the incidence rate. From 1987 to 2001, there was a trend towards treatment with a topical antibiotic (from 43% to 64%), especially fusidic acid cream and mupirocin cream. Treatment with oral antibiotics (from 31% to 14%) and antiseptics (from 11% to 3%) was prescribed less often. Conclusions  We have shown an increased incidence of impetigo in the past decade, which may be the result of an increased tendency to seek help, or increased antibiotic resistance and virulence of Staphylococcus aureus. Further microbiological research on the marked regional difference in incidence may contribute to understanding the factors that determine the spread of impetigo. Trends in prescribing for impetigo generally follow evidence‐based knowledge on the effectiveness of different therapies, rather than the national practice guideline.